F(x) = 1/(x+2) & g(x) = x/(x-3)
(f(x) + g(x) = 1/(x+2) + x/(x-3). Reduce to same denominator:
1/(x+2) + x/(x-3) =(x-3) + x(x-3)/(x+2).(x-3) ==> (x²+3x-3)/(x+2).(x-3)
<em>1) 5 c + 4 = - 26
5 c = -26 -4
5 c = -30
c = -30 / 5
c = -6 so correct option is B..
2) 3 x - x +2 = 12
2 x +2 = 12
2x = 12-2
2x = 10
x = 10/2
x= 5 so correct option is D
3 ) 3 ( x + 1 )+ 6 = 33
3x + 3 + 6 = 33
3x + 9 = 33
3x = 33-9
3x = 24
x = 24/3
x = 8 so correct option is B
4) y/-6=9
y=9 x -6
y= - 54 there is no such option i guess question is missing
5)(x + 4) /2 = 7
x +4 = 7 x 2
x + 4 = 14
x = 14-4
x = 10 so correct option is D
6)1/3 ( 2x - 8) = 4
2x/ 3 - 8 /3 = 4
2x - 8 / 3 = 4
2x - 8 = 4 x 3
2x - 8 = 12
2x = 12 + 8
2x = 20
x = 20/2
x = 10 so correct option is C
</em>
Answer:
Participants were lead to respond in a specific way.
Explanation:
Bias (the verb) is to show influence or prejudice about a certain thing and can cause people to change how they act or what they do.
Are you sure you wrote all the correct numbers because it does not work
70.6 what i got was 70.6753275399